The impact of changes in national prescribing conditions for statins on their public expenditure and utilization in the Czech Republic 1997-2013 - Fuksa, Leos; Vocelka, Milan; Vytrisalova, Magda (Health policy (Amsterdam, Netherlands), 2015)
OBJECTIVES: In the Czech Republic (CZ) extensive price regulation and prescribing conditions are common instruments often employed with new drugs. Since the introduction of statins onto the market in 1990s the originally strict conditions gradually relaxed while the prescription rates and public costs were rising. The aim was to analyze long-term utilization trends of statins, changes in their reimbursement prices and prescribing conditions, and the evolution of the market. METHODS: From January 1997 to December 2013 statin use was measured in terms of defined daily doses per 1000 insured per day (DDD/TID). The prescription-based database of the General Health Insurance Company of the Czech Republic in 1997 covering 7825,216 inhabitants, i.e. 76% of CZ population, was used as the administrative data source. Also the overall expenditure, unit prices, and reimbursement criteria were analyzed. RESULTS: Between 1997 and 2013 the utilization of statins rose from 2 to 96 DDD/TID while the expenditure rose 5.5-fold. The rise of prescription for each molecule was always observed after the liberation of the prescribing criteria. In the study period reimbursement prices of simvastatin and atorvastatin gradually decreased to just 5% of their initial values. CONCLUSIONS: The rising consumption of statins in CZ clearly corresponds in time with the liberation of prescribing conditions allowing for prescription by general practitioners and with the introduction of generics accompanied by a swift and repeated reimbursement price cuts.
Keywords: zdravotní pojištění; Atorvastatin; Statins; lékařská praxe - způsoby provádění; zdravotní politika; simvastatin; Insurance, Health; lidé; dávkové mechanismy; statiny; Drug utilization; Drug Costs; Health insurance reimbursement; Health Policy; Reimbursement Mechanisms; Hydroxymethylglutaryl-CoA Reductase Inhibitors; HMG-CoA reductase inhibitors; atorvastatin; Czech Republic; Drug Substitution; náklady na léky; Česká republika; Treatment costs; náhrada léků; Drug pricing; Simvastatin; Practice Patterns, Physicians'; Humans